Proceedings of the 2016 ACM Symposium on Principles of Distributed Computing 2016
DOI: 10.1145/2933057.2933114
|View full text |Cite
|
Sign up to set email alerts
|

The Greedy Spanner is Existentially Optimal

Abstract: The greedy spanner is arguably the simplest and most well-studied spanner construction. Experimental results demonstrate that it is at least as good as any other spanner construction, in terms of both the size and weight parameters. However, a rigorous proof for this statement has remained elusive.In this work we fill in the theoretical gap via a surprisingly simple observation: The greedy spanner is existentially optimal (or existentially near-optimal) for several important graph families. Focusing on the wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…This loss in the dimension becomes more significant if we restrict the attention to Euclidean spaces, as then the comparison is between Euclidean dimension d and doubling dimension 2d, but spanners for metrics with doubling dimension 2d (or even d) tend to admit significantly weaker guarantees (as a function of and d) than the corresponding ones for d-dimensional Euclidean spaces. Consequently, this result by [25] does not resolve Questions 1 and 2 for two reasons. First, it only implies near-optimality of the greedy spanner, which, as mentioned, comes with a constant factor loss in the dimension, and this constant factor slack appears in the exponents of the size and lightness bounds.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…This loss in the dimension becomes more significant if we restrict the attention to Euclidean spaces, as then the comparison is between Euclidean dimension d and doubling dimension 2d, but spanners for metrics with doubling dimension 2d (or even d) tend to admit significantly weaker guarantees (as a function of and d) than the corresponding ones for d-dimensional Euclidean spaces. Consequently, this result by [25] does not resolve Questions 1 and 2 for two reasons. First, it only implies near-optimality of the greedy spanner, which, as mentioned, comes with a constant factor loss in the dimension, and this constant factor slack appears in the exponents of the size and lightness bounds.…”
mentioning
confidence: 89%
“…Existential near-optimality In PODC'16, Filtser and Solomon [25] studied the optimality of the greedy spanner in doubling metrics, which is wider than the family of low-dimensional Euclidean spaces. They showed that the greedy spanner is existentially near-optimal with respect to both the size and the lightness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the greedy algorithm produces multiplicative spanners with optimal tradeoff between stretch and number of edges. (See also [39].) However, the greedy algorithm is problematic from algorithmic perspective.…”
Section: Setting Definitionsmentioning
confidence: 99%
“…However, since Filtser and Solomon have shown that greedy spanners are (nearly) optimal in their lightness [10], our result implies that the greedy spanner for H-minor-free graphs is also light.…”
Section: Introductionmentioning
confidence: 66%